ADAPTASI VISUAL DAN MATERIAL: PROSES TRANSFORMASI ILUMINASI MANGKUNEGARAN PADA PRODUK INTERIOR LANTAI: VISUAL AND MATERIAL ADAPTATION: TRANSFORMING MANGKUNEGARAN ILLUMINATIONS INTO CONTEMPORARY INTERIOR FLOORING DESIGN - Atridia Wilastrina; Ariani; Cama Juli Rianingrum; Anita Armas (Jurnal Dimensi Seni Rupa dan Desain, 2025)
The visual and material adaptation process of illumination motifs from the ancient manuscripts of Puro Mangkunegaran into interior products, specifically floor surfaces. As part of Javanese visual heritage, manuscript illumination contains rich ornamental forms embedded with symbolic, aesthetic, and spiritual values. Transforming these motifs from manuscript media into flooring requires a design approach that not only involves stylization but also considers functional relevance and material characteristics in a modern context. The process examined includes motif selection and classification, form simplification (stylization), modular repetition and composition, as well as color and scale adjustments tailored to interior visual needs. The stylized motifs are then applied to various flooring materials such as ceramic and natural stone using digital printing and manual techniques. Collaboration with local ceramic industries was carried out to test the technical and aesthetic feasibility of the transformed designs. The results show that adapting Mangkunegaran manuscript illuminations into floor products enriches interior aesthetics while serving as a practical means of cultural preservation in contemporary design. This research recommends further adaptation of traditional visual heritage into other interior elements to promote the integration of local identity within modern spatial design.